Analyzing the response of learners to use kahoot as gamification of learning physics - Anderias Henukh; Yudi Guntara (Universitas Sultan Ageng Tirtayasa, 2020)
This study aims to investigate the response of learners to use Kahoot as a gamification of learning. Kahoot is available for free applications, and this platform can be used in gamification based learning. Kahoot allows educators to make games based on quizzed, surveys, and other things related. Kahoot can be accessed using a smartphone-based on android and ios as well as through a computer with address www.kahoot.it. The method used in this research is descriptive method qualitative data support the results of analyzing the response of pesetas learners. This research was conducted in SMP Tunas Bangsa, West Jakarta learner class VII, with several 16 students. The instrument used in this study was a questionnaire. Instrument used validated using product moment formula and reliability using the formula KR-20. Based on the results of data analysis and discussion, we can conclude that the response of learners in the use Kahoot as gamification of learning that is in the select category with an average overall score obtained is 87.28%.